2019
DOI: 10.1002/cncr.32388
|View full text |Cite
|
Sign up to set email alerts
|

Care delivery, patient experiences, and health outcomes among sexual and gender minority patients with cancer and survivors: A scoping review

Abstract: Sexual and gender minorities (SGMs) face a disproportionate burden of cancer, yet little is known about the experiences and specific needs of these underserved populations in cancer care delivery. The authors conducted a scoping review to characterize the literature on cancer care delivery, health outcomes, and health care experiences for patients with cancer and survivors identifying as SGM. In total, 1176 peer‐reviewed citations were identified after a systematic search of the PubMed/Medline, PsycInfo, Cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 68 publications
1
51
0
1
Order By: Relevance
“…The study did not include studies that focused only on experiences of care (such as patient satisfaction) unless at least one health-related patient-reported outcome was also included as an endpoint. For a recent review that includes studies of patient satisfaction [ 101 ], care decision-making [ 102 , 103 ], provider training for improved SGM care [ 104 ], supportive care needs [ 104 , 105 ], and other disparities affecting SGM persons [ 106 ], see Kent et al [ 107 ]. These studies were not included here, because our focus was on patient-reported outcomes as a result of cancer and treatment rather than satisfaction or care experiences in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The study did not include studies that focused only on experiences of care (such as patient satisfaction) unless at least one health-related patient-reported outcome was also included as an endpoint. For a recent review that includes studies of patient satisfaction [ 101 ], care decision-making [ 102 , 103 ], provider training for improved SGM care [ 104 ], supportive care needs [ 104 , 105 ], and other disparities affecting SGM persons [ 106 ], see Kent et al [ 107 ]. These studies were not included here, because our focus was on patient-reported outcomes as a result of cancer and treatment rather than satisfaction or care experiences in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the potential benefits of technology in this setting, it is important to recognize that the current crisis may pose further challenges to communities that have under "normal circumstances" faced barriers to healthcare access, such as those living in rural environments, as well those low-income, uninsured or underinsured, racial/ethnic minority, and sexual minority medically underserved cancer survivors [27,28]. Whereas for some populations, rapidly developing implementation of telemedicine options may provide new ways to access care and help to break down existing barriers, not all will be served by such measures.…”
Section: Cancer Survivorship Care Deliverymentioning
confidence: 99%
“…To facilitate research on SGM disparities, NIH has encouraged clinics to routinely collect SOGI in the patient electronic record (61). Some clinics have resisted this citing acceptability concerns about their conservative, cisgender, heterosexual patients being offended by being asked about their sexual orientation or seeing a non-binary question on gender.…”
Section: What Is the Easiest Way To Screen For Sexual Orientation And Gender Identity (Sogi)?mentioning
confidence: 99%